Evaluation of gourami farmers’ welfare in the IZI Yogyakarta Smartfarm Program using the CIBEST Method - Sobandi, Liebe; Rakhmawati, Rakhmawati (Journal of Islamic Economics Lariba, 2024)
IntroductionThe integration of productive zakat programs with sector-specific interventions has emerged as a promising strategy for poverty alleviation and community empowerment. In Indonesia, the aquaculture sector, particularly gourami farming, holds significant potential for improving rural livelihoods. However, challenges such as low productivity, economic dependency, and limited market access hinder its growth. Addressing these issues requires innovative programs that align technical, financial, and spiritual support.ObjectivesThis research aims to evaluate the welfare of gourami fish farmers who have received business capital assistance, technical training, and support based on productive zakat. The research was conducted on gourami farmers in Bantul Regency, Yogyakarta Province, who are beneficiaries of the Smartfarm program. The program is managed by the IZI Institution (Indonesian Zakat Initiative) with the support of the XL Axiata Ta’lim Assembly.MethodThis research is a population study, meaning it examines all recipients of the Smartfarm program. The respondents have been participants in the program since November 2022, but only five beneficiaries were successfully studied. Data analysis was conducted using the CIBEST method, which includes the calculation of Material Value (MV) and Spiritual Value (SV) scores. Beneficiaries are classified into four welfare categories based on these scores, namely materially and spiritually prosperous, materially prosperous only, spiritually prosperous only, and not prosperous. The comparison of MV and SV scores before and after the program was conducted to determine changes in welfare.ResultsThe results show that the material value and spiritual value of each mustahik increased after participating in the zakat program. However, the category of mustahik based on the CIBEST quadrant did not change.ImplicationsBy evaluating the welfare changes in recipients of the Smartfarm program, the study highlights the potential benefits and limitations of zakat as a tool for poverty alleviation, particularly within the context of fisheries.Originality/NoveltyThis research contributes to the literature on productive zakat by applying the CIBEST framework in the aquaculture sector, offering a replicable model for addressing multi-dimensional welfare challenges.